Validating nonverbal cues for assessing physician empathy in telemedicine: a Delphi study - Annisa Ristya Rahmanti; Hsuan-Chia Yang; Chih-Wei Huang; Ching-Tzu Huang; Lutfan Lazuardi; Che-Wei Lin; Yu-Chuan Jack Li (Medical Education Online)
Nonverbal communication is essential in physician–patient interaction, especially in telemedicine where verbal cues may be limited. This study aimed to identify and validate key nonverbal cues for assessing physician empathy in telemedicine consultations through a Delphi method. A three-round Delphi study was conducted from June to November 2022, involving various experts, including academics, healthcare professionals, AI/telemedicine researchers, industry professionals, and patients. Experts evaluated the importance, validity, and reliability of potential nonverbal cues. Consensus was determined based on median responses and expert scoring percentages, with statistical agreement and stability assessed using Kendall’s coefficient of concordance (Kendall’s W) and Wilcoxon signed-rank test. Analyses were conducted using SPSS, version 23.0 with significance set at p < 0.05. Of the 72 experts invited, 37 (51%) agreed to participate, with 35 completing the first round (95% completion rate). Eight significant nonverbal cues were identified in the first round, though one did not reach consensus. The second round obtained an 89% response rate (31/35), with three new cues introduced; one did not reach consensus. Round 3 achieved a 94% response rate (29/31), finalizing nine key cues: facial expression, eye contact, tone of voice, smiling, head nodding, body posture, hand gesture, distance, and environmental cues. Among these, facial expression, eye contact, and tone of voice were identified as the most crucial. Inter-expert agreement was statistically significant across all items with strong agreement on the importance (W = 0.739, p < 0.001), good agreement on their validity (W = 0.689, p < 0.001), and moderate agreement on their reliability (W = 0.452, p < 0.001). This study highlights the importance of specific nonverbal cues in telemedicine, particularly facial expression, eye contact, and tone of voice. It provides a validated foundation for developing tools to enhance physician–patient interactions and potentially improve health outcomes in telemedicine.